Activation of naloxone-sensitive and -insensitive inhibitory systems in a human pain model - Koppert, Wolfgang; Filitz, Jörg; Tröster, Andreas; Ihmsen, Harald; Angst, Martin; Flor, Herta; Schüttler, Jürgen; Schmelz, Martin (The journal of pain, 2005)
We investigated naloxone effects in a model of electrically induced pain and hyperalgesia. In a double-blind, placebo-controlled, cross-over study, 15 volunteers underwent four 150-minute sessions of high-current-density electrical stimulation of their forearms. After 60 minutes, naloxone or placebo was given intravenously (increasing plasma concentrations of 0.1, 1, and 10 ng/mL; 30 minutes each) in 3 of the 4 sessions. Pain ratings and areas of mechanical hyperalgesia were assessed at regular intervals during all sessions. The low doses of naloxone did not cause any significant change of pain rating of areas of hyperalgesia. In terms of intrasession effects, pain ratings and areas of hyperalgesia significantly decreased during the sessions to 62% (pain rating), 70% (area of punctuate hyperalgesia), and 82% (area of allodynia) of the initial values. Naloxone (10 ng/ml) reversed these decreases. In terms of between-session effects, the time course of pain ratings remained constant from session to session. In contrast, the areas of punctate hyperalgesia successively decreased to 60% of initial value at the fourth repetition. The session effect was not reversed by naloxone. High-current-density electrical stimulation provokes central sensitization, but in addition inhibitory systems are activated that are only partly naloxone-sensitive. - Perspective - Endogenous inhibitory systems are of major importance for clinical pain conditions, but are not reflected in traditional human pain models. Here we show activation of a naloxone-sensitive short-term and a naloxone-insensitive long-term inhibitory system in a new model of electrically induced pain and hyperalgesia.
Gesehen am 05.11.2020